Easy Access to 2-Fluoro- and 2-Iodo-2H-azirines via the Halex Reaction - Agafonova, Anastasiya V.; Smetanin, Ilia A.; Rostovskii, Nikolai V.; Khlebnikov, Alexander F.; Novikov, Mikhail S. (Synthesis, 2019)
A simple gram-scale method for the preparation of esters and dialkylamides of 2-(fluoro/iodo)-2H-azirine-2-carboxylic acids via the halogen exchange (Halex) reaction of 2-bromo-substituted analogues is reported. The method operates with inexpensive and safe reagents, Bu4NF and potassium iodide, providing high product yields. Alternatively, 2-fluoro-2H-azirine-2-carboxylates can be prepared from 2-iodo- and 2-chloro-analogues. The latter compounds can be obtained in practically quantitative yield by treating the 2-iodo- and 2-bromo-2H-azirine-2-carboxylic esters with Bu4NCl.
Keywords: azirines; halogen exchange reaction; fluorine; iodine; nucleophilic substitution